Bacterial Cellulose Synthesis by Gluconacetobacter xylinus: Enhancement via Fed-batch Fermentation Strategies in Glycerol Media - Adnan, Azila; Nair, Giridhar; Lay, Mark; Swan, Janis (Trends in Sciences, 2021)
Bacterial cellulose (BC) is an abundant polysaccharide, which is secreted by several genera of bacteria. It has remarkable characteristics, which include high purity, high tensile strength, high biocompatibility and non-toxic. The main feature that differentiates BC and plant cellulose (PC) is the absence of contaminants such as lignin, hemicellulose and pectin. However, the main drawbacks in producing BC are low yield and expensive carbon source. Due to that, this study was carried out to enhance BC volumetric productivity in fed-batch operation mode using glycerol as a carbon source. BC was produced in fill-and-draw and pulse-feed fed-batch cultures of Gluconacetobacter xylinus DSM 46604 in a 3-L bench-top bioreactor. The fed-batch fermentation trials were conducted in agitated and aerobic conditions at 30 ºC. For fill-and-draw fed-batch culture, a total of 24.2 g/L of BC accumulated in the bioreactor after 9 days, which corresponded to a yield and productivity of 0.2 g/g and 2.69 g/L/day, respectively. Pulse-feed fed-batch fermentation resulted in a yield and volumetric productivity of 0.38 g/g and 2.71 g/L/day, respectively. The pulse-feed fed-batch culture proved to be a better fermentation system for utilizing glycerol, which is a low-cost and abundant carbon source. HIGHLIGHTS Komagataeibacter species, which were formerly known as Acetobacter or Gluconacetobacter is one of the Gram-negative BC producers that secretes a large quantity of BC microfibrils extracellularly One of the main challenges in bacterial cellulose (BC) production is low productivity and high processing cost As fed-batch fermentation is one of the operation modes in bioprocess that can control the microbial growth rate, this operation mode is conducted to enhance the yield of BC, substrate consumption and also volumetric productivity Fill-and-draw and pulse feed fed-batch culture were conducted to enhance yield and volumetric productivity. The pulse-feed fed-batch culture resulted to be a favorable operation mode for utilizing glycerol, which is a low-cost and abundant carbon source GRAPHICAL ABSTRACT